What is genius - Daly, Corinne Louise (My University, 1893)
Introduction: In every age the whole world regards the rising of a genius with wonder, admiration and praise. His very presence brings to our minds this question. Why should this man rise above us when we have had the same advantages. The best answer is incomplete. That genius is hereditary few people doubt, but there arises this question. Why is genius suddenly present in families who for generations before could neither read nor write. That genius is a divine gift, (is a popular idea) [author intended to omit the text inside the parentheses] requiring no special effort on the part of its posessor to produce marvelous results in Art, Lit and Science is often proved to be a mistake. Does anyone suppose that Newton’s valuable discoveries were the result of but a moments thought Newton it is said worked thirteen years before publishing the barest outline of his discoveries. Do you suppose that the battleplans of Gen. Grant were impromptu?
Citation: Daly, Corinne Louise. What is genius. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Genium; Literature and science; Art; Newton; Grant; Theses; Manuscripts (documents)